The Analysis of Directive Speech acts Used in English Textbook Entitled Bahasa Inggris Textbook for Senior High School Grade XI - Nabila, Zulfa; As'ad, Muhammad (English Education and Literature Journal (E-Jou), 2023)
Directive shows a strong relationship between speaker and hearer moreover in the textbook that used by the students and teacher in the teaching and learning process. This research investigated the directive speech acts used in Bahasa Inggris textbook for senior high school grade XI. Descriptive qualitative of document study method was implied in this research. The source of data in this research is Bahasa Inggris textbook for senior high school grade XI published by Indonesian Ministry of Education and Culture. Document analysis was used to collect the data. The steps are looking for the English textbook entitle Bahasa Inggris textbook for senior high school grade XI, then reading the textbook and analyze the directive speech acts in the English textbook. The researcher used theory of Kreidler (1998) to analyze the type of directive speech acts. In this research, the researcher applied the technique of data analysis based on Miles, et al. (2014) theories. The data were analyzed through three steps, those are data condensation, data display and conclusion drawing/verification. The result showed that 93 data of directive speech acts are found in the textbook. Command is the most frequent type of directive speech acts that appear in the textbook. The total of command is 70 data or 75,26% while request only appears three times or 3,24% in the textbook. There are 20 data or 21,50% suggestions those are used in the textbook to ask the students doing something in the teaching and learning activities. From this result, it is anticipated that teachers would be able to utilize more directing strategies to encourage students to actively think through and respond to questions from the teacher related to the textbook.Keywords: speech acts, directive speech acts, textbook